Good Practices in National Systems for Environmental and Social Impact Assessment : A Literature Review - World Bank (Washington, DC, 2022)
National systems for environmental and social impact assessment (ESIA) are designed to improve the environmental and social performance of projects and support countries’ sustainable development strategies. The objectives of this Literature Review are to identify trends, findings and gaps in global literature focused on national systems for ESIA. The Review analyzes global ESIA literature to inform the World Bank’s response to Borrower country requests for assistance in strengthening national systems for ESIA, provide input to broader World Bank country strategies and identify priority areas for future World Bank engagement. The Review concludes with recommendations for how the World Bank Group can support Borrower countries, in partnership with civil society, proponents and the public, in efforts to strengthen national systems for ESIA. This review focuses on literature related to national systems for ESIA as opposed to individual ESIA reports. A national system for ESIA is defined by the Netherlands Commission for Environmental Assessment (NCEA) as: (i) the regulatory environment, (ii) the capacity of organizations within that environment and (iii) the quality of a set of core functions necessary for effective ESIA. In this way, national systems extend beyond a single ESIA report or process and encompass both the assessment of environmental and social impacts as well as the implementation of processes to manage and monitor these impacts. It visualizes how national systems for ESIA are rooted in goals and principles and involve a range of relevant actors and standards which are incorporated into the scope of this review.